Analysis of archive of scientific hydrometeorological information of the Ukrainian Antarctic station Academic Vernadskiy - S. V. Klok (Ukrainian Antarctic Journal, 2012)
Analysis of electronic archive of the hydrometeorological data got at the Antarctic station FaradayAcademic Vernadsky educed some lacks of his organization and, accordingly, related to it possible problems of further storage, treatment and use of data. The ways of decision of the mentioned problems are offered.